PEMBELAJARAN DARING MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Awaludin, Agus Muhamad; Supriatna, Tatang; Nurjaman, Adi (IKIP Siliwangi, 2023)
This study aims to examine the scenario and implementation of online learning, the reaction of teachers and students to learning, the difficulties felt by students in completing the problem, as well as the obstacles experienced by teachers when doing online learning material system of linear equations two variables using CTL approach. This study is a qualitative descriptive research. This study was conducted on 20 students of SMP Plus Darul Amanah Ciwidey. The results of the study went as planned, the teacher's reaction when the learning process got a score of 94% which included very good criteria, it can be seen from the results of teacher observation sheets carried out each learning meeting, the student's reaction to learning got an average score of 71% with a very good category. The difficulty experienced by students in working on a system of linear equations of two variables lies in the difficulty of skills, concepts, and principles. The obstacles experienced by teachers when carrying out learning are varied such as students who do not have internet quotas, expensive internet payments, signal constraints, lack of student motivation, and lack of supervision from parents during the learning process.